Mindestlohn: Marktmacht, Preisüberwälzung und Aufstocken - eine Erwiderung - Dominik Groll; Stefan Kooths (Wirtschaftsdienst, 2014)
In der Augustausgabe 2013 veröffentlichte der Wirtschaftsdienst einen Aufsatz von Dominik Groll und Stefan Kooths mit dem Titel Vor der Bundestagswahl: Argumente für Mindestlöhne überzeugen nicht. Jürgen Kromphardt setzt sich hier kritisch mit ihren Argumenten auseinander. Daraufhin erläutern die Autoren ihren Standpunkt in einer Erwiderung. – – This article by Jürgen Kromphardt argues against the view that the introduction of a legal minimum wage of exteuro8.50 per hour for all jobs will result in a massive reduction of jobs. He finds the theoretical foundation of this forecast very shaky, because the assumptions of this model are not fulfilled in the real world. It is thus unsurprising that empirical analyses do not corroborate it. Groll and Kooths respond that neither demand-side market power in the labour market nor supply-side price-setting capacity in the goods market are sufficient reasons to justify the introduction of minimum wages. They reiterate the major arguments both in the narrow environment of a static market model and in a more enriched framework that puts human action in the centre of economic analysis. They also show that topping up low incomes within the German ALG II transfer system can hardly be considered a wage subsidy
Keywords: J23; J31; J38; 330